2018
DOI: 10.5897/jdae2016.0726
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of microfinance loan utilization by smallholder farmers: The case of Omo Microfinance in Lemo District of Hadiya Zone, Southern Ethiopia

Abstract: This study investigated factors determining microfinance loan utilization by smallholder farmers from Omo Microfinance institution in Lemo District of Hadiya Zone, Southern Ethiopia. Both primary and secondary data were used and a total of 118 sampled farmers were considered for the interview. Both descriptive statistics and independent double-hurdle model were used to analyze the microfinance loan utilization and loan amount received. The results showed that literacy status, household size, size of landholdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…As presented in Table 7, the majority (76%) of the smallholder farmers perceived the payback period to be long (long -24% and very long -52%) meaning they preferred a short payback period. The findings were consistent with the ones of Chauke et al (2013) and Ayele and Goshu (2016) who revealed that access to credit is negatively influenced by the perception of the loan repayment period. Therefore, long payback periods are more applicable to businesses that produce and sell throughout the whole year, not to seasonal economic activities as agriculture.…”
Section: Smallholder Farmers' Perceptions Towards Payback Period (Ppp)supporting
confidence: 92%
“…As presented in Table 7, the majority (76%) of the smallholder farmers perceived the payback period to be long (long -24% and very long -52%) meaning they preferred a short payback period. The findings were consistent with the ones of Chauke et al (2013) and Ayele and Goshu (2016) who revealed that access to credit is negatively influenced by the perception of the loan repayment period. Therefore, long payback periods are more applicable to businesses that produce and sell throughout the whole year, not to seasonal economic activities as agriculture.…”
Section: Smallholder Farmers' Perceptions Towards Payback Period (Ppp)supporting
confidence: 92%
“…This result was consistent with Argaw (2017) who found that a one-unit increase in the farmer's education level resulted in a 0.033 increase in the farmer's likelihood of obtaining credit from microfinance institutions (MFIs). There was a positive relationship between the education level of farmers and the probability of accessing to credit (Amanuel & Degye, 2018;Asante-Addo et al, 2013;E. Saqib et al, 2018;Mohamed, 2003;Mulatu et al, 2020).…”
Section: Educationmentioning
confidence: 99%
“…Amanuel and Degye [11] examined the determinants of smallholder farmers' use of microfinance loans in the Lemo district of the Hadiya area, Southern Ethiopia: the case of Omo microfinance. The researcher observed that sex, literacy status, level of income, level of savings, the intent of loan taking and perception of loan repayment were significant factors influencing the number of loans obtained.…”
Section: Introductionmentioning
confidence: 99%